2011
DOI: 10.1002/ajpa.21581
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Tunisian ethnic groups revealed by paternal lineages

Abstract: Tunisia has experienced a variety of human migrations that have modeled the myriad cultural groups inhabiting the area. Both Arabic and Berber-speaking populations live in Tunisia. Berbers are commonly considered as in situ descendants of peoples who settled roughly in Palaeolithic times, and posterior demographic events such as the arrival of the Neolithic, the Arab migrations, and the expulsion of the "Moors" from Spain, had a strong cultural influence. Nonetheless, the genetic structure and the population r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
8
31
0
Order By: Relevance
“…The YCC nomenclature [47] was used throughout the manuscript. The Tunisian populations [39] were pooled into one group since Analysis of the Molecular Variance (AMOVA) showed them to be genetically homogeneous (variation among groups  = 0.70%, p>0.05 and 1.50%, p>0.05 for Y-STR and Y-SNP, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The YCC nomenclature [47] was used throughout the manuscript. The Tunisian populations [39] were pooled into one group since Analysis of the Molecular Variance (AMOVA) showed them to be genetically homogeneous (variation among groups  = 0.70%, p>0.05 and 1.50%, p>0.05 for Y-STR and Y-SNP, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…J2 is very frequent in the Levant/Anatolia/Iran region [37] and its spread in the Mediterranean is believed to have been facilitated by the maritime trading culture of the Phoenicians (1550 BC- 300 BC) [38]. In contrast to the Middle Eastern influence, studies have reported only limited contribution of sub-Saharan paternal lineages to the North African gene pool [39], [40]. Previous analyzes of mtDNA lineages in North African populations suggest significant Eurasian origins [41][43] with lineages dating back to Paleolithic times [41] and with recent gene flow from sub-Saharan Africa linked to slave trade [44].…”
Section: Introductionmentioning
confidence: 99%
“…Northwest Africa (100% in the Berber group from Chenini-Douiret and Jradou, Tunisia; 80% in Mozabite Berbers from Algeria; 76% in Saharawis from Western Sahara; 65-73% in Berbers from Morocco) (Arredi et al, 2004;Cruciani et al, 2004;Semino et al, 2004;Robino et al, 2008;Fadhlaoui-Zid et al, 2011) while their frequencies decline sharply towards the east (5% in North Egypt) as Berber groups (Sengupta et al, 2006) dwindle. In…”
Section: E-m81 and E-m183mentioning
confidence: 96%
“…Based on haplogroup distribution, the genetic pool of the North African populations is made up of two components: the Berber genetic impact of the autochthonous inhabitants of the region (haplogroup E-M81) added to the Arabic one (haplogroup J1-M267), brought to North Africa by gene flow from the Middle East (Fadhlaoui-Zid et al, 2011;Robino et al, 2008;TrikiFendri et al, 2015). In fact, it is well known that the distribution of E-M81 in Africa is highly related to the regions inhabited by Berber-speaking populations, suggesting a close haplogroup-ethnic group parallelism (Cruciani et al, 2004).…”
Section: Discussionmentioning
confidence: 98%